CIM in the context of smart cities: how the interoperability between BIM and SIG can assist the development of smart cities. - Dias, Alvaro Jose; de Oliveira, João Paulo Leonardo (Revista Nacional de Gerenciamento de Cidades, 2021)
Nowadays, Smart Cities are one of the most debated and discussed subjects related to urban development. Various technological and innovative processes are being integrated into society’s everyday life, aiming at fulfilling the new demands for a sustainable growth that is led by the citizens, by and large. In this context, the infrastructure sector figures as one of the most important points to reach that goal. This paper seeks to study the applicability of the Building Information Modeling (BIM), and of the Geographic Information System (GIS) to Smart Cities, highlighting the main potentialities and challenges of the utilization of these processes. The study will be realized through a literature review of the most relevant works, focusing on the integration of technologies and placing the concepts of City Information Modeling (CIM) in the discussion. It is our understanding that the adoption of CIM concepts by city managers, and by the entire construction sector, could be an important step in the development of Smart Cities around the world.